Effects of supplemental UV-B radiation on photosynthesis performance and UV-B absorbing compounds in leaves of two oak species - Mészáros, Ilona (Acta Biologica Szegediensis, 2005)
The aim of this work was to compare the photosynthetic responses of two tree species (Quercus petraea, Quercus robur) and to determine the leaf level protection under enhanced UV-B radiation in outdoor experiments. Three year old seedlings of both species were exposed to enhanced UV-B radiation (supplementing the ambient level with 40%) from bud break until leaf senescence. Under enhanced UV-B, increases of specific leaf mass (SLM) and reduction of leaf chlorophyll content per dry weight basis were observed but the total carotenoid content remained high. Both oak species responded with an increase of VAZ pool to enhanced UV-B. High values of potential photochemical efficiency of PS2 (Fv/Fm) were observed in both species during the growing season. On clear sunny days loss of Fv/Fm was observed from morning till midday which was larger under enhanced UV-B for both species suggesting that UV-B exposure enhanced the sensitivity of seedlings to photoinhibition. The enhanced UV-B induced increases in the amount of UV-B absorbing compounds in leaves of Q. robur but it slightly affected these traits of leaves of Q. petraea.